The Influence of Organizational Culture on the Performance Efforts of Pusdatin Employees to Support the Main Tasks of Pusdatin Kemhan - Karmila, Thia; Romauli, Rentina; Rahmawati, Rahmawati; Hakim, Azis (Dinasti Publisher, 2024)
Every organization has efforts to improve employee performance in order to create competent personnel, so it is necessary to make efforts to support Human Resources which is the main effort of the organization in improving employee performance, this is because Human Resources is an important role holder who has responsibility big to improve it, the organization carries out socialization, training/training, work discipline, a good work environment, good work motivation for employees to increase the competence of employees who have high loyalty and responsibility to the organization. Improving the performance of human resources is also very important to pay attention to, one of which is implementing the policies of an effective leader of an organization. Case studies were carried out at the Ministry of Defense Data and Information Center. The research method uses a descriptive qualitative approach and employees who work in the Pusdatin environment are required to be able to shows good performance. Leadership actors play a very important role in overall efforts to improve performance, both at the individual, group and organizational levels.